The Influence Of Brand Ambasador And Instagram Advertising On Zoya Cosemtic Product Purchase Decisions (Case Study On Follower Instagram @Zoyacosmetics) - Sutama Wisnu Dyatmika; Mertha Viviani; Wira Yudha Alam (Universitas Muhammadiyah Sorong, 2021)
A brand is an inanimate object so that a living being is needed to represent it, on the basis of this, the brand is associated in the form of a brand ambassador (BA). BA is often massively published on the social media platform Instagram and the majority of brands use paid partnerships with Instagram. This pattern of influence will be interesting if it is associated with product purchase decisions with zoya cosmetic objects.This study aims to analyze the influence of Brand Ambassador and Instagram Ads on purchasing decisions for Zoya cosmetic products (Case study on @zoyacosmetics Instagram follower). This study uses quantitative methods, and uses a sample of 115 respondents. To test the results of the questionnaires, the researchers used a validity test with a significance result of 5% or 0.005 and a reliability test with a Cronbach alpha result of 0.968 for brand ambassadors, 0.964 for Instagram ads, and 0.895 for purchasing decisions. belong to this study there are results from hypothesis testing with a significance value of 0.000. From the results that have been obtained, it shows that BA and Instagram ads have a significant and positive effect simultaneously on purchasing decisions for Zoya cosmetic products.